The View from the Borderlands: U.S. Foreign Policy and September 11th - Borkowski, Alexandra G. (URJ-UCCS: Undergraduate Research Journal at UCCS, 2011)
Two significant contributions to the September 11th political dialogue are Arundhati Roy’s essay "The Algebra of Infinite Justice" and Mohsin Hamid's novel The Reluctant Fundamentalist. The South Asian perspectives supplied by both Roy and Hamid are valuable to American readers because the authors present ideas not generally acknowledged in mainstream American media. The critical analyses offered by Roy and Hamid focus on U.S. foreign policy and its connection to the September 11th attacks. The authors are concerned with how the United States conducts itself in the world politically, economically, and militarily. Both examine the harmful consequences of U.S. foreign policy in developing countries, and use Afghanistan as an example.